Icariin, but Not Genistein, Exerts Osteogenic and Anti-apoptotic Effects in Osteoblastic Cells by Selective Activation of Non-genomic ERα Signaling - Ho, Ming-Xian; Poon, Christina C.-W.; Wong, Ka-Chun; Qiu, Zuo-Cheng; Wong, Man-Sau (Frontiers in Pharmacology, 2018)
Genistein and icariin are flavonoid compounds that exhibit estrogen-like properties in inducing bone formation and reducing bone loss associated with estrogen deficiency in both preclinical and clinical studies. However, the mechanisms that are involved in mediating their estrogenic actions in bone cells are far from clear. The present study aimed to study the signaling pathways that mediate the estrogenic actions of genistein and icariin in osteoblastic cells. The effects of genistein and icariin on the activation of estrogen receptor (ER) and the downstream MAPK and PI3K/Akt signaling pathway in murine osteoblastic MC3T3-E1 cells and rat osteoblastic UMR-106 cells were studied. As expected, genistein displayed higher binding affinity towards ERα than ERβ and significantly induced estrogen response element (ERE)-dependent transcription in UMR-106 cells in a dose-dependent manner. In contrast, icariin failed to bind to ERα or ERβ and did not induce ERE-dependent transcription in UMR-106 cells at 10-10 to 10-7M. The effects of genistein (10 nM) and icariin (0.1 µM) on cell proliferation and differentiation in osteoblastic UMR-106 cells were abolished in the presence of ER antagonist ICI 182,780 (1 µM), MAPK inhibitor U0126 (10 µM) and PI3K inhibitor LY294002 (10 µM). Genistein at 10 nM rapidly induced ERK1/2 phosphorylation at 5 to 10 min in UMR-106 cells and the phosphorylation of ERα at both Ser118 and Ser167 in both MC3T3-E1 and transfected UMR-106 cells whereas icariin at 0.1µM rapidly activated both ERK1/2 and Akt phosphorylation in UMR-106 cells and subsequent ERα phosphorylation at both Ser118 and Ser167 in MC3T3-E1 and transfected UMR-106 cells. Confocal imaging studies confirmed that the phosphorylation of ERα at Ser 118 and Ser 167 by genistein and icariin in MC3T3-E1 cells was mediated via MAPK- and PI3K- dependent pathway, respectively. Furthermore, our studies showed that icariin exerted stronger anti-apoptotic effects than genistein and 17β-Estradiol (E2) and inhibited the cleavage of downstream caspase-3 in MC3T3-E1 cells induced by a potent PI3K inhibitor, PI828 (at 2 µM). These results indicated that the mechanisms that mediate the estrogenic actions of icariin in osteoblastic cells are different from those of genistein.